Humoral and T-cell-mediated responses to an insect-specific flavivirus-based Zika virus vaccine candidate. - Danielle L Porier; Awadalkareem Adam; Lin Kang; Pawel Michalak; Juselyn Tupik; Matthew A Santos; Manette Tanelus; Krisangel López; Dawn I Auguste; Christy Lee; Irving C Allen; Tian Wang; et al. (PLoS Pathogens)
Flaviviruses represent a significant global health threat and relatively few licensed vaccines exist to protect against them. Insect-specific flaviviruses (ISFVs) are incapable of replication in humans and have emerged as a novel and promising tool for flavivirus vaccine development. ISFV-based flavivirus vaccines have shown exceptional safety, immunogenicity, and efficacy, however, a detailed assessment of the correlates of protection and immune responses induced by these vaccines are still needed for vaccine optimization. Here, we explore the mechanisms of protective immunity induced by a previously created pre-clinical Zika virus (ZIKV) vaccine candidate, called Aripo/Zika (ARPV/ZIKV). In brief, immunocompromised IFN-αβR-/- mice passively immunized with ARPV/ZIKV immune sera experienced protection after lethal ZIKV challenge, although this protection was incomplete. ARPV/ZIKV-vaccinated IFN-αβR-/- mice depleted of CD4+ or CD8+ T-cells at the time of ZIKV challenge showed no morbidity or mortality. However, the adoptive transfer of ARPV/ZIKV-primed T-cells into recipient IFN-αβR-/- mice resulted in a two-day median increase in survival time compared to controls. Altogether, these results suggest that ARPV/ZIKV-induced protection is primarily mediated by neutralizing antibodies at the time of challenge and that T-cells may play a comparatively minor but cumulative role in the protection observed. Lastly, ARPV/ZIKV-vaccinated Tcra KO mice, which are deficient in T-cell responses, experienced significant mortality post-challenge. These results suggest that ARPV/ZIKV-induced cell-mediated responses are critical for development of protective immune responses at vaccination. Despite the strong focus on neutralizing antibody responses to novel flavivirus vaccine candidates, these results suggest that cell-mediated responses induced by ISFV-based vaccines remain important to overall protective responses.